(untitled) - Patrick R. SCHMIDLIN; Phillip MÜLLER; Thomas ATTIN; Marco WIELAND; Deborah HOFER; Bernhard GUGGENHEIM (University of São Paulo, 2013)
ObjectiveTo investigate the microbial adherence and colonization of a polyspecies biofilm on 7 differently processed titanium surfaces.Material and MethodsSix-species biofilms were formed anaerobically on 5-mm-diameter sterilized, saliva-preconditioned titanium discs. Material surfaces used were either machined, stained, acid-etched or sandblasted/acid-etched (SLA). Samples of the latter two materials were also provided in a chemically modified form, with increased wettability characteristics. Surface roughness and contact angles of all materials were determined. The discs were then incubated anaerobically for up to 16.5 h. Initial microbial adherence was evaluated after 20 min incubation and further colonization after 2, 4, 8, and 16.5 h using non-selective and selective culture techniques. Results at different time points were compared using ANOVA and Scheffé post hoc analysis.ResultsThe mean differences in microorganisms colonizing after the first 20 min were in a very narrow range (4.5 to 4.8 log CFU). At up to 16.5 h, the modified SLA surface exhibited the highest values for colonization (6.9±0.2 log CFU, p<0.05) but increasing growth was observed on all test surfaces over time. Discrepancies among bacterial strains on the differently crafted titanium surfaces were very similar to those described for total log CFU. F. nucleatum was below the detection limit on all surfaces after 4 h.ConclusionWithin the limitations of this in vitro study, surface roughness had a moderate influence on biofilm formation, while wettability did not seem to influence biofilm formation under the experimental conditions described. The modified SLA surface showed the highest trend for bacterial colonization.